2019
DOI: 10.1525/elementa.362
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying methane emissions in the Uintah Basin during wintertime stagnation episodes

Abstract: This study presents a meteorologically-based methodology for quantifying basin-scale methane (CH4) emissions in Utah’s Uintah Basin, which is home to over 9,000 active and producing oil and natural gas wells. Previous studies in oil and gas producing regions have often relied on intensive aircraft campaigns to estimate methane emissions. However, the high cost of airborne campaigns prevents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…The Horsepool and Roosevelt monitors are situated at lower elevation in the basin and are frequently exposed to high methane in the winter when emissions are trapped under cold-pool conditions. The Fruitland monitor is situated at a higher elevation and does not see similarly high methane enhancements 27 . Figure 2B compares the TROPOMI methane columns between December 2018 and March 2019 with data from the three monitors.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The Horsepool and Roosevelt monitors are situated at lower elevation in the basin and are frequently exposed to high methane in the winter when emissions are trapped under cold-pool conditions. The Fruitland monitor is situated at a higher elevation and does not see similarly high methane enhancements 27 . Figure 2B compares the TROPOMI methane columns between December 2018 and March 2019 with data from the three monitors.…”
Section: Resultsmentioning
confidence: 95%
“…We conclude that the TROPOMI hotspot observed over the Uintah Basin is caused by enhanced methane in the boundary layer in agreement with surface monitors. Continued surface and TROPOMI measurements over the Uintah Basin will be useful to further develop and evaluate emissions estimates under cold-pool conditions 27 , which can then be applied with more confidence for other, similar basins. permian basin.…”
Section: Resultsmentioning
confidence: 99%
“…UUCON collects near-surface data used to (a) understand spatial and temporal variability of emissions (Pataki et al, 2003(Pataki et al, , 2005Mitchell et al, 2018b;, (b) evaluate the accumulation of pollutants during complex meteorological conditions (Pataki et al, 2005;Gorski et al, 2015;Baasanbdorj et al, 2017;Fiorella et al, 2018), (c) develop and improve atmospheric transport models (Strong et al, 2011;Nehrkorn et al, 2013;Mallia et al, 2015), (d) validate emissions inventory estimates (McKain et al, 2012;, (e) investigate relationships between urban emissions and air pollution (Baasandorj et al, 2017;Mouteva et al, 2017;, and (f) inform stakeholders and policymakers (Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in the Permian Basin observed entire months where coverage was sparse in certain locations [19], and arial and tower measurements with gridded ONG production data between January and August 2020 were used to estimate methane fluxes in several small targeted subregions of the Basin, but a limited number of satellite estimates over their targeted regions precluded any direct comparisons between observations and TROPOMI [19]. Better determining which ONG regions and basins can be utilized for TROPOMI satellite observations, which ones have too high surface reflectance or too frequent cloud or snow cover, and which basins have ground observations to validate satellite data against will all be important considerations in the future analysis of TROPOMI CH 4 retrievals over these regions [25,69]. Using satellite data in concert with multiple in situ measurements to validate the results is also recommended as future work.…”
Section: Discussionmentioning
confidence: 99%